BUILDING STRATEGIC CAPABILITY IN ENHANCING COMPETITIVE ADVANTAGE: EVIDENCE FROM BANK BJB IN INDONESIA’S DIGITAL BANKING TRANSFORMATION - Natal Indra; Syukron Sazly; Suryanto Sosrowidigdo (Dynamic Management Journal, 2026)
This study examines how digital capability, strategic agility, and innovation capability contribute to the competitive advantage of Bank BJB amid intensifying digital banking competition in Indonesia. The rapid growth of financial technology (fintech), the QRIS ecosystem, artificial intelligence (AI)-based banking services, and changing customer behavior has accelerated digital transformation across the banking industry. This study adopts a qualitative descriptive case study approach using secondary data collected from annual reports, banking industry publications, government reports, and credible media sources. The findings indicate that Bank BJB has strengthened its digital banking ecosystem, customer-oriented service innovation, and strategic responsiveness through mobile banking expansion, QRIS integration, digital payment systems, and operational digitalization initiatives. These capabilities collectively enhance organizational competitiveness, adaptability, operational efficiency, and long-term sustainability. The study recommends strengthening AI-driven banking services, cybersecurity systems, fintech collaboration, and digital customer experience. The study is limited by its qualitative approach and reliance on secondary data.